Identify the Region's Flagship Products: Focused on the Sustainability of Resources and the Environment - Mandataris Mandataris; Okta Karneli; Syofiatul Safitri (Universitas 17 Agustus 1945 Semarang, 2024)
The purpose of this research is to identify in Mak Teduh Village, where most of the area consists of peatland with oil palm, rubber, and acacia plantations, the local potential that can be developed into superior products for the village as a means to enhance the community's economy through development focused on the sustainability of resources and the environment. The identification method is applied by the OVOP (One Village One Product) criteria and SWOT analysis. The results of the research indicate several local potentials that can be developed into superior products, namely creative industries in the form of pandan leaf crafts and crafts from recycled plastic, fisheries such as salted fish, and livestock including acacia honey cultivation. In addition, there is also the potential for tourism that can be developed. Based on the OVOP criteria and SWOT analysis, the potential of the village that can be developed as a flagship product is in the cultivation of acacia honey. The availability of land and bee feed in acacia and palm plantations, as well as opportunities in national and international markets, means that acacia honey cultivation also provides a chance for communities to engage in sustainable businesses while enhancing public awareness of forest and environmental conservation. The cultivation of acacia honey also serves as a preventive solution to the cases of forest and peatland fires that frequently occur in Mak Teduh Village.